Anatomopathological characterization of hepatocellular carcinoma in a jaguar (Panthera onca) - de Moura, Fernanda Barthelson Carvalho [UNESP]; Benevenuto, Luíz Guilherme Dercore [UNESP]; Rocha, Noeme Sousa [UNESP]; Cagnini, Didier Quevedo [UNESP] (Springer Nature, 2025)
A 21-year-old jaguar (Panthera onca) with a low body score, pale ocular mucosa, severe dehydration, and decubitus eschar was referred to our veterinary hospital. The patient died and underwent a postmortem examination to establish a diagnosis. Macroscopic evaluation revealed a reddish-black, well-defined, focally extensive mass measuring 12 cm in diameter on the visceral surface involving the left lateral lobe of the liver. The mass was surrounded by a capsule and exhibited diffuse hemorrhage, cystic areas, infiltrative zones on cross-section, and areas of morphologically compatible fatty liver degeneration. The primary differential diagnoses included adenoma, hepatocellular carcinoma, and cholangiocarcinoma. Microscopic analysis showed malignant hepatocytes forming irregular trabeculae of two or more cells, with vascular spaces between them, rudimentary acini, and neoplastic cell aggregates scattered throughout the parenchyma. Additional findings included coagulative necrosis, macrophage infiltration, hepatocyte cord formation, moderate pleomorphism, anisokaryosis, and the presence of discrete binucleated and multinucleated cells. To our knowledge, this is the first report of hepatocellular carcinoma in a jaguar. This information may aid veterinary pathologists in reporting hepatic alterations and characterizing anatomopathological findings in jaguars, representing a valuable contribution to the literature.
Keywords: Hepatic tumor; Pathology; Wildlife